Chromosome-level assemblies of the endemic Korean species Abeliophyllum distichum and Forsythia ovata - Hoyeol Jang; Ara Cho; Hyuk-Jin Kim; Haneul Kim; Seung-Hoon Jeong; Sun Mi Huh; Hee-Ju Yu; Dong-Kab Kim; Joo-Hwan Kim; Jeong-Hwan Mun (Scientific Data)
Abstract Abeliophyllum distichum and Forsythia ovata are closely related species endemic to Korea and are highly valued as ornamental shrubs in the Oleaceae family. A combination of PacBio and Illumina sequencing with Hi-C scaffolding technologies was employed to develop chromosome-level genome assemblies of these species. The assembled genome sizes are 795.72 Mb for A. distichum and 1,108.53 Mb for F. ovata. The assemblies exhibit scaffold N50 lengths of 53.12 Mb and 68.97 Mb, with minimal gaps measuring 323.40 kb and 149.00 kb, and 97.71% and 98.82% BUSCO scores for Embryophyta single-copy orthologs, respectively, indicating high contiguity and completeness. The genomes contain 485.24 Mb and 691.68 Mb of repetitive sequences, 4,926 and 7,175 full-length long terminal repeat retrotransposons, and 49,414 and 57,587 protein-coding genes, respectively. The 14 pseudochromosomes encompass 93.80% of the A. distichum genome and 89.11% of the F. ovata genome, thereby demonstrating one-to-one chromosome-level collinearity. These high-quality genome assemblies serve as invaluable resources for genetic and breeding studies, facilitating a deeper understanding of the evolutionary history of these distinctive species.